Академічна мобільність майбутніх фахівців у контексті іноваційних методологічних підходів - Циганаш, А.В. (Культура народов Причерноморья, 2013)
У даній статті розглядаються сучасні тенденції розвитку методології наукового пізнання світу з сенергетичної позиції світосприйняття, а також зовнішні чинники, які сприяють розвитку академічної мобільності майбутніх фахівців в контексті безперервної освіти. В данной статье рассматриваются современные тенденции развития методологии научного познания мира с позиции сенергетической картины мира, а также внешние факторы, которые способствуют развитию академической мобильности будущих специалистов в контексте непрерывного образования. This article discusses the current trends of methodology development of scientific world experience in terms of globe synergy, as well as external factors that contribute to the development of academic mobility of future professionals in the context of continuing education. The topicality of the research of academic mobility problems of future specialists within the framework of continuous education is determined by different factors. It is, at first, weak knowledge of society about scientific research of this area. Secondly, an increasing outflow of the Ukrainian students abroad with high-performance progress which causes reduction of scientific and intellectual potential in national higher educational establishments. Thirdly, the movement of the educational national systems within the framework of Bologna process to the unique criteria and standards which are set within the framework of European educational space. According to these standards, educational and research orientation is taken into account while determining the universities ratings. An important moment in development of students’ academic mobility is scientification of educational process. Scientification is not only the use of scientific information in studies; it includes a wider spectrum of relations: interrelation of educational process and science. It is different aspects of methodology of scientific cognition, which together with information about science promote an improvement of educational process. Thus, synergistic approach means the world perception as an aggregate of nonlinear processes. This process has direct influence on forming a new style of scientific thought.